2008
DOI: 10.2135/cropsci2007.05.0274
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Indirect Selection for Dry Matter Yield Based on Fresh Matter Yield in Perennial Ryegrass Sward Plots

Abstract: Forage dry matter yield (DMY) is a high‐priority trait in breeding perennial ryegrass (Lolium perenne L.). However, determining dry matter concentration is highly labor intensive. For a similar level of resources, indirect selection based on fresh matter yield (FMY) would allow a greater number of replicates, genotypes, or both to be evaluated. Our objective was to estimate the efficiency of indirect selection for DMY based on FMY of pure perennial ryegrass sward plots. Over a 14‐yr period, replicated trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
8
8
0
Order By: Relevance
“…The decrease of residual variance in the second year may be related to a better establishment that makes the cutting conditions more homogeneous, thereby reducing the measurement error. The heritabilities estimated in this paper mostly agree with other publications in sward plots (Frandsen, 1986; Devey et al, 1989; Ravel and Charmet, 1996; Conaghan et al, 2008b). However, the estimates in this paper often appear to be more precise, due to the relatively large amount of data that were included.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The decrease of residual variance in the second year may be related to a better establishment that makes the cutting conditions more homogeneous, thereby reducing the measurement error. The heritabilities estimated in this paper mostly agree with other publications in sward plots (Frandsen, 1986; Devey et al, 1989; Ravel and Charmet, 1996; Conaghan et al, 2008b). However, the estimates in this paper often appear to be more precise, due to the relatively large amount of data that were included.…”
Section: Discussionsupporting
confidence: 90%
“…The low phenotypic correlations between the same cuts in two consecutive years was also shown by Conaghan et al (2008b), who reported a small predictability for the yield in the second year based on first-year data. This result could be due to the fact that some families actually produce more in the first year and less in the second year and vice versa.…”
Section: Forage Yieldsupporting
confidence: 58%
See 1 more Smart Citation
“…The ability to select for genotypes that will be higher quality at maturity based on a trait measured before flowering would increase the efficiency and rate of gain that can be made from selection on a per-year basis. Successful indirect selection has been demonstrated for various traits and crops [7,44]. In these studies, greater selection responses were observed when the heritability of the trait to be evaluated as well as the correlation between the indirect and direct targets of selection were relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…In perennial ryegrass ( Lolium perenne L.), FMY is routinely used as the principal selection criterion for forage yield plots under both conservation and frequent‐harvest managements, owing to relationships between FMY and DMY that are similar to those observed in the current study (Conaghan et al, 2008). The Conaghan et al (2008) study similarly showed that heritability of FMY and DMY were similar and that an increase in the number of genotypes is required to allow FMY to achieve a greater rate of gain than DMY. Otherwise, for both the ryegrass and switchgrass studies, use of FMY is nothing more than a labor‐saving approach.…”
Section: Discussionmentioning
confidence: 52%